Microfinance Development in Uzbekistan : Technical Note - World Bank (World Bank, Washington, DC, 2017)
The Government of Uzbekistan has requested the World Bank to provide observations and recommendations for development of the microfinance market in Uzbekistan. This includes credit unions and microfinance organizations (MFOs), and touches on ‘consumer lending’ or small loans originated by commercial banks. For purposes of this Policy Note, the discussion focuses on issues pertaining to the non-bank institutions active in microfinance, as well as those that relate to the banks’ existing efforts in this segment of the market. There is no particular focus on other groups, such as micro-leasing, micro-savings, micro-insurance, or agricultural credit cooperatives that are often included in separate categories, because they either are not active in Uzbekistan or data are not available for them. Current legislation envisions some of these activities unfolding, namely micro-leasing and micro-insurance. However, as of late 2006, early 2007, these were not included as part of the assessment. This policy note on microfinance does not address larger issues regarding the macro-economy or banking sector, as this discussion falls outside the scope of understanding between the Government of Uzbekistan (henceforth GoU) and the Bank. At the same time, there are references to some of the key macro and structural issues that impact developments in microfinance, namely inflation and interest rates at the macro level, and the incentive framework for banks and non-banks specific to microfinance.